2018
DOI: 10.1093/ndt/gfy150
|View full text |Cite
|
Sign up to set email alerts
|

Superior vena cava stenosis in haemodialysis patients with a tunnelled cuffed catheter: prevalence and risk factors

Abstract: SVC stenosis is not a rare condition, is mostly asymptomatic in the absence of a peripheral VA, is strongly associated with diabetes and is promoted by long TCC carriage. Age is slightly protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…Their retrospective study found SVC stenosis occurs at a rate of 0.14 cases/1000 catheter days corresponding to 1.8 episodes per year in a center of 100 hemodialysis patients. However, the majority of SVC stenosis was diagnosed in the setting of catheter malfunction with only two cases diagnosed by the classical symptoms of SVC syndrome including facial and upper extremity edema [5]. While rare the development of chylothorax alone carries a mortality of 10% in most major medical centers [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their retrospective study found SVC stenosis occurs at a rate of 0.14 cases/1000 catheter days corresponding to 1.8 episodes per year in a center of 100 hemodialysis patients. However, the majority of SVC stenosis was diagnosed in the setting of catheter malfunction with only two cases diagnosed by the classical symptoms of SVC syndrome including facial and upper extremity edema [5]. While rare the development of chylothorax alone carries a mortality of 10% in most major medical centers [2].…”
Section: Discussionmentioning
confidence: 99%
“…Many cases present as a result of thrombosis around the catheter leading to SVC obstruction requiring removal of the catheter and long-term anticoagulation. The other common cause of SVC syndrome is SVC stenosis best defined as a diameter reduction >50% with or without upstream collaterals [5]. We report a case of SVC stenosis in an end stage renal disease (ESRD) patient on hemodialysis with a chronically indwelling left jugular central catheter leading to both chylothorax and chylopericardium.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the use of catheters, pacemakers and implantable cardioverter defibrillator (ICD) leads have contributed to this. This results in fibrosis, inflammation of the venous wall, and eventually, stenosis of the SVC 8–10…”
Section: Discussionmentioning
confidence: 99%
“…Vascular access remains the Achilles' heel of hemodialysis (HD), and a functional arteriovenous fistula (AVF), a concept invented by American physicians of Italian descent in the early sixties, can not be created in all HD patients. Thus, the use of HD catheters, despite the multiple associated risks [1,2], especially catheter-related blood stream infections (CRBSIs), is unavoidable.…”
mentioning
confidence: 99%